Pelatihan Penentuan Harga Pokok Produksi Produk UMKM - alfian, alfian sayuti; R. Ayu Ida Aryani; Defel Septian; Farha (Insan Kreasi Media, 2022)
MSMEs in Mataram City in 2020 amounted to 22,473 which makes it the highest number compared to MSMEs in the Regency and City of West Nusa Tenggara Province. The number consists of 15,746 Micro classes, 6,194 Small, and 533 medium classes. There are still many micro-enterprises in Mataram and the class must be upgraded to Small or Medium Enterprises. This becomes complex related to capital, sales strategy, and Annual Turnover to increase company profits. Increasing company profits can be achieved by optimizing profits. MSMEs in the production sector sometimes find it difficult to determine the cost of production. The service is carried out by teaching the cost of the production program through the asynchronous method. The Chairperson and Members visit MSME traders who have processed products and processed raw materials into finished goods that are ready to be sold. The service mechanism is carried out in several stages including, FGD with the service team and partners, partner interviews, making the cost of production, making presentations recorded through the Zoom application, and will be shared on Google Drive, sending Google Drive links to service partners.